ANALISIS KEBUTUHAN SISTEM INFORMASI DALAM PENGELOLAAN KAWASAN WISATA SANUR - Ni Wayan Rena Mariani; Firlie Lanovia Amir; I Gusti Ayu Eka Suwintari (Institut Pariwisata dan Bisnis Internasional, 2017)
Trends of Information System affect the tourism industry. This fact showed by the utilization of information and communication technology used in the tourism industry. In the 1960s Flight Industry (Airlines) introduced the Central Reservation system. The mid-1990s tourism information system developed into a destination management system (DMS). The system was developed to provide information about tourism product to the tourist and used to find out the number of visitors. With this data, the destination management organization can make efforts to attract more visitors to come to the tourism destination Sanur is a one tourism destination that located in Bali Island. Geographically the sanur tourism destination is located in the southern part of the island of Bali. Administratively, sanur is a kelurahan in Denpasar Sub district, Denpasar municipality area. The main attraction of Sanur is the natural form of beaches along approximately 7 km from the start of the Matahari Terbit beach to the Mertasari Beach. Sanur Tourism Area is an area that is growing very rapidly. The growth of sanur area needs to be followed by good management to avoid exploitation of the Area.Good management requires valid and complete data to be able to make the right decision forÂ developing of sanur tourism area. In the management of tourist areas, obtaining valid data is not an easy job, because it involves many parties and data changes fast enough. To obtain a valid data need a Information system, so that data can be kept updated continuously.This article discusses the analysis of information system needs for sanur destination management. The discussion in this article aims to find the concept of information systems needed. The method used in data collection is interview and observation method. Data were analyzed by using linear and hierarchy technique with 6 stages.The results of this discussion is a concept of information systems with databases to be able to provide the data as a needed of the management sanur tourism area.